Numerical CFD Analysis of an Aerodynamic Head Cover of a Rotorcraft Motor - Szwedziak, Katarzyna; Lusiak, Tomasz; Grzywacz, Zaneta; Drozd, Kacper (Communications - Scientific Letters of the University of Zilina, 2018)
Autogyros can become an alternative for the use of rotorcrafts in various fields of life, including agroforestry. They have better economic performance than helicopters, owing to, among other things, the presence of a bearing rotor. Most autogyros also have other advantages in terms of no need for the compliance with stringent regulatory regulations - with respect to new constructions, lower combustion, noise and emissions of toxic elements. The cover of the bearing rotor head is an important element of rotorcrafts, which demonstrates that aerodynamics plays an important role in aerodynamic designs. Therefore, in this article, air flow model testing is carried out for two types of the bearing rotor blades of an autogyro with and without a cover using the ANSYS Fluent program. An aerodynamic drag analysis was also performed.
Keywords: CFD numerical analysis; autogyro; aerodynamic cover; rotor head